1989
DOI: 10.1172/jci114085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous free radicals on electromechanical function and metabolism in isolated rabbit and guinea pig ventricle. Implications for ischemia and reperfusion injury.

Abstract: Oxygen-derived free radicals have been implicated in the pathogenesis of cardiac dysfunction during ischemia, postischemic myocardial "stunning," and reperfusion injury. We investigated the effects of oxygen-derived free radicals on cardiac function in intact isolated rabbit hearts and single guinea pig ventricular myocytes. In the intact rabbit ventricle, exposure to free radical-generating systems caused increased cellular K+ efflux, shortening of the action potential duration, changes in tension, and deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
5

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 51 publications
4
69
1
5
Order By: Relevance
“…The generation by the physiological mechanism of Ca2+-activated cross-bridge cycling (24). ATP depletion has been reported as a consequence ofexposure to exogenous free radicals (9,19), but the reported depletion in bulk ATP to -50% of control levels would not in itself suffice to produce contracture (45 (33). Metabolism: effect offree radicals on high energy phosphates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation by the physiological mechanism of Ca2+-activated cross-bridge cycling (24). ATP depletion has been reported as a consequence ofexposure to exogenous free radicals (9,19), but the reported depletion in bulk ATP to -50% of control levels would not in itself suffice to produce contracture (45 (33). Metabolism: effect offree radicals on high energy phosphates.…”
Section: Resultsmentioning
confidence: 99%
“…Direct recordings of membrane potential (14,15) and ionic currents (9,16) during and after exposure to free radicals reveal surprisingly specific effects on ion transport pathways, with no evidence for the creation of nonspecific leaks. Goldhaber et al (9) have found that radicals generated either by hydrogen peroxide or by xanthine + xanthine oxidase turn on ATP-sensitive potassium channels in the sarcolemma. Since these channels are thought to be preferentially regulated by ATP derived from glycolysis (rather than from oxidative phosphorylation), the observation that they are activated by exogenous free radicals is suggestive of glycolytic inhibition (17).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, the inward rectifying K + current has been reported to be either unaffected (Cerbai et al, 1991) or decreased (Tarr & Valenzeno, 1991). The electrophysiological effects of ROS generally consist of a reduction in action potential amplitude and an increase in action potential duration followed by a reduction (Tarr and Valenzeno, 1989;Barrington, 1994;Satoh and Matsui, 1997), although either only a reduction (Goldhaber et al, 1989;Hayashi et al, 1989;Coetzee et al, 1990) or only an increase in action potential duration (Barrington, 1994) have also been reported. Nakaya et al (1991) reported that ROS-induced shortening of the action potential duration of guinea-pig isolated ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, voltagedependent Na + , K + and Ca 2+ channels, Ca 2+ -activated K + channels, and K ATP channels have all been identified as targets for ROS (Hool, 2006). Several previous studies indicate that H 2 O 2 alters energy metabolism, ATP-sensitive K + currents, L-type Ca 2+ currents (Goldhaber & Liu, 1994;Racay et al, 1997), as well as delayed rectifier K + currents (Goldhaber et al, 1989). However in literature the data concerning the effect of ROS on potassium current are controversal.…”
Section: Wwwintechopencommentioning
confidence: 99%